1995
DOI: 10.1080/00288233.1995.9513132
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogenesis potential and iodine concentration in white clover (Trifolium repensL.) cultivars

Abstract: Hydrogen cyanide (HCN) and iodine (I) concentrations in the herbage were determined for 51 white clover (Trifolium repens L.) cultivars that had been grown under uniform conditions in a glasshouse. HCN contents ranged from 120 to 1110ngHCN/g dry matter (DM). Cultivars that are agronomically successful in New Zealand, and cultivars of New Zealand origin, were mainly highly cyanogenic. There was evidence in 'Grasslands Kopu' and 'Aran' of a decline in cyanide content in plants raised from first generation seed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 17 publications
2
68
0
3
Order By: Relevance
“…Figure 4 suggests that although there might be some inter-varietal differences in I concentrations in some crops, they might be small compared to inter-specific differences. This supports conclusions of previous studies with numerous varieties of clover, grasses and other herbage crops [23,25,32]. Nevertheless, further analyses might very usefully compare the amount of variation above and below the species level in order to determine the extent to which I concentrations in plant biomass can be altered by choosing different varieties or different species.…”
Section: Beta Vulgarissupporting
confidence: 59%
“…Figure 4 suggests that although there might be some inter-varietal differences in I concentrations in some crops, they might be small compared to inter-specific differences. This supports conclusions of previous studies with numerous varieties of clover, grasses and other herbage crops [23,25,32]. Nevertheless, further analyses might very usefully compare the amount of variation above and below the species level in order to determine the extent to which I concentrations in plant biomass can be altered by choosing different varieties or different species.…”
Section: Beta Vulgarissupporting
confidence: 59%
“…Numerous authors have reported observations for defense functions of plant cyanogenesis against herbivores (e.g., Nahrstedt, 1985Nahrstedt, , 1988Hruska, 1988;Jones, 1962Jones, , 1988Jones, , 1998Crush and Caradus, 1995;Caradus and Forde, 1996;Schappert and Shore, 1999b,c;Tattersal et al, 2001). However, clear experimental results considering quantitative aspects of the action of HCN as causal factor of plant defense are rare (Feeny, 1976;Patton et al, 1997;Gleadow and Woodrow, 2000a,b).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true if the conserved silage/hay was fed in conjunction with crops containing goitrogens, such as swedes, turnips, and kales. In addition, there appears to be an emerging problem of I deficiency as reported by , and probably caused by the modern clover selections (Crush & Caradus 1995). Increasing the I status of silage/hay to adequate levels (>0.25 mg kg -1 ; Morton et al 1999), would be likely to result in improved reproductive performance and lower perinatal lamb mortality rates Grace et al 2001).…”
Section: Discussionmentioning
confidence: 99%